2016
DOI: 10.1080/14739879.2016.1149957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of revalidation on appraisal in primary care: an initial evaluation of the experience of Welsh GPs

Abstract: The study participants reported that revalidation had impacted on appraisal, bringing increased time and costs alongside some increased individual reflection and Quality Improvement (QI) activity. The impact was felt more by appraisers than appraisees. Overall, of those GPs revalidated in 2013, 62% reported it was a positive experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Negative feelings about the process obtained here are in keeping with findings of previous work looking at appraisal and revalidation (Middlemass & Siriwardena 2003;Dale, Potter, Owen & Leach, 2016;Williams, Holmes & Laugharne, 2016; The Uk Medical Revalidation Evaluation CoLLAboration (UMbRELLA), 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Negative feelings about the process obtained here are in keeping with findings of previous work looking at appraisal and revalidation (Middlemass & Siriwardena 2003;Dale, Potter, Owen & Leach, 2016;Williams, Holmes & Laugharne, 2016; The Uk Medical Revalidation Evaluation CoLLAboration (UMbRELLA), 2016).…”
Section: Discussionsupporting
confidence: 87%
“…However, the programme has been criticised as being too time‐consuming and intrusive . Other, perhaps less controversial, models exist to accomplish the same ends …”
Section: Discussionmentioning
confidence: 99%
“…This echoes other findings: a survey of ROs found that they considered participation in QI and responses to significant events as the most effective methods of improving doctor performance; 28 the large online survey conducted by UMbRELLA found CPD was the most commonly reported change as a result of appraisal; 17 another survey of GPs also cited QI and SEAs as important in prompting changes, with colleague feedback also regarded as important in helping deeper reflection on their work (though it should be noted that they valued patient feedback almost as much). 29 The latest GMC guidance emphasises the central role of reflection in appraisal and describes it in terms of a twin process, stating that: "your appraiser can facilitate further reflection, as needed but it is your responsibility to demonstrate examples of your reflective practice." 11 So firstly, each doctor needs to produce written reflective accounts and then there is an expectation that this will be reflected upon further in the appraisal -both to increase the depth of the learning and satisfy the appraiser that meaningful reflection has taken place.…”
Section: Discussionmentioning
confidence: 99%